Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1007/s11743-998-0050-2
|View full text |Cite
|
Sign up to set email alerts
|

Mixed micelles of cationic surfactants and bile acid salts in aqueous media

Abstract: Critical micelle concentrations of cetyltrimethylammonium-p-toluene sulfonate (CTAT) and cetylpyridinium chloride (CPC) with sodium cholate (NaC) and sodium deoxycholate (NaDC) were determined in aqueous solutions by surface tension measurements. Interaction parameters and mole fraction of the components in mixed micelles were estimated using Rubingh's theory. Strong interaction was observed for each mixed system, a common feature shown by anionic-cationic mixtures. Dramatic effects on the viscosities of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
(31 reference statements)
3
9
0
Order By: Relevance
“…, solutions having α CPM = 0.3, 0.5, 0.7, and 0.9 were turbid solutions. A similar observation was reported for different cationic + anionic surfactants (Barry and Gray, ; George et al, ; Jana and Moulik, ; Maiti et al, ; Maiti et al, ; Manna et al, ; Vethamuthu et al, ; Vethamuthu et al, ). It was reported that cetyltrimethylammonium chloride + SDC and cetyltrimethylammonium bromide (CTAB) + SDC with close to 0.5 mol fraction formed turbid mixtures, which led to phase separation upon standing over time (Barry and Gray, ; George et al, ; Vethamuthu et al, , ).…”
Section: Resultssupporting
confidence: 83%
“…, solutions having α CPM = 0.3, 0.5, 0.7, and 0.9 were turbid solutions. A similar observation was reported for different cationic + anionic surfactants (Barry and Gray, ; George et al, ; Jana and Moulik, ; Maiti et al, ; Maiti et al, ; Manna et al, ; Vethamuthu et al, ; Vethamuthu et al, ). It was reported that cetyltrimethylammonium chloride + SDC and cetyltrimethylammonium bromide (CTAB) + SDC with close to 0.5 mol fraction formed turbid mixtures, which led to phase separation upon standing over time (Barry and Gray, ; George et al, ; Vethamuthu et al, , ).…”
Section: Resultssupporting
confidence: 83%
“…As can be seen in Table 3, the b parameters for mixed monolayer formation and micelle formation are negative which means that all systems show synergism. These results are consistent with observations of other researches [20,[22][23][24] that the interactions between oppositely charged surfactant are strongly attractive due to the electrostatic forces between the two different hydrophilic head groups. Moreover, similar trends are also found in the interactions between two different surfactants in mixed micelles which are generally weaker than their interactions in mixed monolayers at the aqueous solutionair interface.…”
Section: Molecular Interactions and Synergismsupporting
confidence: 93%
“…The interaction between anionic-cationic surfactants is generally very strong, but such systems often lead to precipitation/coacervation due to the coulombic interactions between the oppositely charged species. We have recently reported studies on a few mixed surfactant systems composed of oppositely charged, similarly charged, and ionicnonionic surfactant systems (19,20). The results were in good agreement with those reported in the literature.…”
supporting
confidence: 87%
“…However, to our knowledge, few studies have documented anionic-nonionic mixed surfactant systems (11)(12)(13)19,21) despite considerable interaction being reported for these mixed systems. Besides, investigations demonstrating the influence of counter-ion valence on the interactions between surfactant molecules in the mixed micelle of the mixed surfactant system are scarce (8,18,20). Thus, investigating nonionic-anionic mixed surfactant systems with an emphasis on the influence of counter-ion valence on the nature and strength of interactions in these systems seemed worthwhile.…”
mentioning
confidence: 99%